Offbeat otolaryngology : what they didn't teach you in medical school - Bennett, John D. C. (John D. Courtenay) (Thieme, 2001)
Want to get a step up on the competition? This is the book for young doctors trying to bluff their way into erudite otolaryngological circles by giving the impression ...